The THE IMPORTANCE OF REACHING ADULTHOOD FOR BUILDING A HARMONIOUS FAMILY IN ISLAMIC MARRIAGES IN INDONESIA - Arifin, Syamsul (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2025)
Early marriage rates in Indonesia are relatively high. This is quite ironic, considering that marriage is not merely about conducting a ceremonial union, but also about bearing the responsibility of building a good family with the hope of achieving sakinah, mawaddah, and warahmah (peace, love, and compassion). A new development has occurred in Indonesia with the enactment of Undang-Undang No 16 Tahun 2019, which amends Undang-Undang No 1 Tahun 1974 on Marriage. The main emphasis of Undang-Undang No 16 Tahun 2019is the revision of the minimum age requirement for marriage. Early marriage has negative impacts both psychologically and in terms of health. Entering marriage at an adult age plays a vital role in minimizing the potential negative effects associated with early marriage. This, in turn, helps pave the way for a harmonious and peaceful family life.